2012
DOI: 10.4103/0970-0358.101319
|View full text |Cite
|
Sign up to set email alerts
|

Burn wound: How it differs from other wounds?

Abstract: Management of burn injury has always been the domain of burn specialists. Since ancient time, local and systemic remedies have been advised for burn wound dressing and burn scar prevention. Management of burn wound inflicted by the different physical and chemical agents require different regimes which are poles apart from the regimes used for any of the other traumatic wounds. In extensive burn, because of increased capillary permeability, there is extensive loss of plasma leading to shock while whole blood lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
213
1
19

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(236 citation statements)
references
References 22 publications
3
213
1
19
Order By: Relevance
“…Comparing self-inflicted razor and sodium sulfide (chemical burn) wounds, Bishop observed that chemical wounding kills cells below the level at which dead tissue is produced (Bishop 1945). Similarly, thermal injuries extend beyond the initial burn (Tiwari 2012), and if no adequate measure is taken to improve microcirculation around the initial burn, the adjacent zone of stasis (i.e. where microcirculation has stopped but cells are not quite dead) will undergo necrosis a few days post-burn.…”
Section: Sequence Of Events Leading To Wound Closurementioning
confidence: 99%
“…Comparing self-inflicted razor and sodium sulfide (chemical burn) wounds, Bishop observed that chemical wounding kills cells below the level at which dead tissue is produced (Bishop 1945). Similarly, thermal injuries extend beyond the initial burn (Tiwari 2012), and if no adequate measure is taken to improve microcirculation around the initial burn, the adjacent zone of stasis (i.e. where microcirculation has stopped but cells are not quite dead) will undergo necrosis a few days post-burn.…”
Section: Sequence Of Events Leading To Wound Closurementioning
confidence: 99%
“…[25]. Sources of pathogens that are able to infect the burn wounds are from the respiratory and gastrointestinal flora, endogenous and the environment [26]. Good nutrition following burns is advisable since it promotes wound healing.…”
Section: Antimicrobialsmentioning
confidence: 99%
“…This leaves the victims in the danger of activating an undesired immune response if the material used does not have hemocompatible properties. 1 The typical host response triggered by the synthetic material includes the formation of thrombosis, inflammation, and foreign body reaction. This will further delay the healing process which usually take years for complete epithelization and maturation.…”
Section: Hemocompatibility Of Bio-nanofibrous Dressing Materialsmentioning
confidence: 99%
“…Pain and the generalized effects on the body experienced by a burn victim are incomparable with other traumas. [1][2][3][4] Initial pathophysiological events associated with burn wound healing include hemostasis and onset of a prolonged inflammatory phase. This leads to the release of several proteins, and formation of edema and exudate at the wound site.…”
Section: Introductionmentioning
confidence: 99%